WIND POWER GENERATION SYSTEM, DEVICE USING WIND POWER GENERATION SYSTEM, AND METHOD FOR OPERATING SAME - AZEGAMI KENICHI; MATSUNOBU TAKASHI; YANAGIBASHI TAKUJI; SAKAMOTO KIYOSHI (2014)
It is an object to provide a wind turbine able to generate power irrespective of a presence of and a state of a power grid. To achieve the above object, a wind power generation system is provided with a wind turbine, the wind turbine including a blade 5 that rotates in response to the wind, a generator 7 that rotates with rotation of the blade 5 to generate power, and an auxiliary machine that controls a pitch angle of the blade 5. The auxiliary machine is driven by the generated power of a downwind type wind turbine to which a permanent magnet type generator 12 is mounted and which generates power in a state in which a blade 10 of the downwind type wind turbine rotating in response to the wind faces downwind.